Efficacy and Safety of Intranasal Dexmedetomidine vs. Oral Chloral Hydrate for Sedation in Children Undergoing Computed Tomography/Magnetic Resonance Imaging: A Meta-Analysis - Lyu, Xiaoqian; Tao, Yujuan; Dang, Xiujing (Frontiers in Pediatrics, 2022)
OBJECTIVE: This meta-analysis aims to evaluate the sedative efficacy and safety of intranasal administration of dexmedetomidine (DEX) compared with oral chloral hydrate for Computed tomography (CT) or Magnetic Resonance Imaging (MRI) examination in Children. METHODS: Cochrane Library, PubMed, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), and China WanFang Databases were searched to collect randomized controlled trials (RCTs) investigating intranasal DEX (test group) versus oral chloral hydrate (control group) in pediatric CT/MRI examinations up to December 30, 2021. The data were analyzed using Stata 15.0 software. RESULTS: Seven RCTs with 1846 children were identified. The meta-analysis results showed that the success rate of sedation (RR = 1.14, 95% CI: 1.03 to 1.26, P = 0.011), sedation onset time (weighted mean difference (WMD) = -0.87, 95% CI: -1.42 to -0.31, P = 0.002), sedation duration ( WMD = -9.05, 95% CI:-14.69 to -3.42, P = 0.002), time to awakening (WMD = -9.75, 95% CI:-17.57 to -1.94, P = 0.014), and incidence of nausea and vomiting (relative risk (RR) = 0.09, 95% CI:0.04 to 0.23, P < 0.001) of the test group were significantly better than those of the control group. However, no significant differences were identified in incidence of hypotension (RR = 1.18, 95% CI: 0.51 to 2.74) and bradycardia (RR = 1.17, 95% CI: 0.13 to 22.11) between the two groups. CONCLUSION: Intranasal administration of DEX is superior to oral chloral hydrate for sedation during pediatric CT/MRI examinations and has a better safety profile.